Safe Tractor Operations: Tractor Operator Checklist: AE604, 6/2024 - Gorucu, Serap; Lehtola, Carol J.; Brown, Charles M. (EDIS, 2024)
An operator checklist is provided at the end of this publication from the Safe Tractor Operations series. This checklist is designed so that it can be kept as a record of a tractor operator’s training. Written by Serap Gorucu, Carol J. Lehtola, and Charles M. Brown, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2024.